2021
DOI: 10.1039/d0sm02104k
|View full text |Cite
|
Sign up to set email alerts
|

Strain- and field-induced anisotropy in hybrid elastomers with elongated filler nanoparticles

Abstract: The implementation of anisotropy to functional materials is a key step towards future smart materials. In this work, we evaluate the influence of preorientation and sample architecture on the strain-induced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The influence of the particle shape on the material properties has not been sufficiently explored. Recently, several experimental works that focused on the response of polymer composites containing elongated and platelet filler particles have been published [ 80 , 81 , 82 , 83 ]. It was shown that the magnetorheological effect can be enhanced using anisometric filler.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the particle shape on the material properties has not been sufficiently explored. Recently, several experimental works that focused on the response of polymer composites containing elongated and platelet filler particles have been published [ 80 , 81 , 82 , 83 ]. It was shown that the magnetorheological effect can be enhanced using anisometric filler.…”
Section: Introductionmentioning
confidence: 99%